Regulations and Procedures for Establishing Banks in Saudi Arabia - Assery , Essa Ali Mohammed (Dirasat: Shari’a and Law Sciences, 2020)
Banks are one of the key pillars of all countries and their establishment is subject to the competent authorities and requires the fulfillment of the conditions, controls and procedures necessary for this. This research clarifies the controls and legal and regulatory procedures for the establishment of banks in Kingdom of Saudi Arabia and demonstrating the provisions for obtaining the banking license and the legal and regulatory procedures applicable and coordination with the competent authorities in order to show the role of Kingdom of Saudi Arabia in the application of Islamic law (Sharia). Also, it highlights the role of Saudi Arabian Monetary Authority (SAMA) as the Central Bank of Saudi Arabia in the supervision and control of banks. It has been appeared to the researcher through this research that banks are an indispensable cornerstone of countries, states, societies, its stability, its survival and its ability to adapt to events and developments particularly that this matter requires tightening and controlling the necessary rules and regulations and procedures necessary for its establishment. The study found that banks in the kingdom of Saudi Arabia are governed by rules and principles derived from Islamic Sharia, which is the basis for the rest of the legal and regulatory rules aimed at regulating banking work. The study recommended amending the paid-up capital required to establish and establish banks in accordance with the current economic situation and allowing institutions and natural persons with high financial capacity to invest in banks.